2013
DOI: 10.1371/journal.pone.0056407
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Protects against LPS-Induced Acute Lung Injury by Inactivation of NF-κB

Abstract: BackgroundNuclear factor-κB (NF-κB) is a central transcriptional factor and a pleiotropic regulator of many genes involved in acute lung injury. Andrographolide is found in the plant of Andrographis paniculata and widely used in Traditional Chinese Medicine, exhibiting potently anti-inflammatory property by inhibiting NF-κB activity. The purpose of our investigation was designed to reveal the effect of andrographolide on various aspects of LPS induced inflammation in vivo and in vitro.Methods and ResultsIn viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
150
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 34 publications
6
150
0
Order By: Relevance
“…It binds specifically to the DNA binding subunit p50 at Cys 62 residue of the NF-kB complex, preventing the complex from binding to DNA for gene transcription (39). It has been shown that andrographolide suppressed LPS-induced p65 phosphorylation, p65 nuclear translocation, and NF-kB DNA binding activity in mouse MEL-12 epithelial cells and Raw 264.7 cells (40,41). However, in the present study andrographolide could not inhibit combined LPS/IFN-g-stimulated p65 phosphorylation in the Raw 264.7 cell line (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It binds specifically to the DNA binding subunit p50 at Cys 62 residue of the NF-kB complex, preventing the complex from binding to DNA for gene transcription (39). It has been shown that andrographolide suppressed LPS-induced p65 phosphorylation, p65 nuclear translocation, and NF-kB DNA binding activity in mouse MEL-12 epithelial cells and Raw 264.7 cells (40,41). However, in the present study andrographolide could not inhibit combined LPS/IFN-g-stimulated p65 phosphorylation in the Raw 264.7 cell line (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of alcohol consumption have been linked to an increased inflammatory response, including increased cytokine release (14,15,37,38). Pro-inflammatory cytokines such as IL-1β, TNF, IL-6 and IL-8 have been identified as important contributors to the pathogenesis of organ damage, including lung as well as liver injury in models of acute inflammation (17)(18)(19)(39)(40)(41)(42). Together with IL-6, IL-8 binds to molecules that are involved in neutrophil activation, trafficking and infiltration of tissues in models of acute lung and liver injury (18,43).…”
Section: Discussionmentioning
confidence: 99%
“…0.05 in inactive elastase-treated arteries postoperative at day 14). The in vivo dosage of Andro in the literature ranges from 1 to 100 mg/kg body weight, with 5 mg/kg body weight (used in the current study) as a commonly used dosage, which is considerably lower than the LD 50 for intraperitoneally administered andrographolide (11.6 g/kg body weight) (Handa and Sharma, 1990;Wang et al, 2007;Hsieh et al, 2011;Zhu et al, 2013). At the selected time points, mice were euthanized by CO 2 inhalation.…”
Section: Methodsmentioning
confidence: 99%